Renovation Strategies for Green Spaces in Aging Residential Communities in Cold Regions to Enhance Carbon Sequestration and Wellness - Xia Rong; Haonian Fang; Chunlin He (Buildings)
This study explores renovation strategies for green spaces in aging residential communities in cold regions, with a particular focus on enhancing carbon sequestration capacity and residents’ well-being. Under the framework of the “dual carbon” goals, a combination of literature analysis and resident surveys reveals that (1) the existing layouts of green spaceand plant selections have not fully considered their carbon sequestration potential, leaving significant room for optimization; (2) low outdoor temperatures, the lack of heating facilities, and monotonous winter landscapes contribute to reduced green space utilization, limiting outdoor activities and diminishing the health benefits of green spaces; and (3) the integration of glass sunrooms with renewable energy systems, such as photovoltaic power generation, can effectively improve winter green space utilization, regulate micro climates, and enhance vegetation-based carbon sequestration while also providing residents with comfortable spaces for social interaction and wellness activities. The findings indicate that scientifically optimizing green space layouts, selecting plant species with high carbon sequestration potential, and incorporating climate-adaptive architectural designs can significantly enhance the ecological value of green spaces and residents’ quality of life. It is recommended that future community renewal initiatives integrate green technologies, policy support, and interdisciplinary collaboration to promote low-carbon and livable urban development.